"I'm not doing what I should be doing as a midwife": An ethnographic exploration of central fetal monitoring and perceptions of clinical safety. Issue 2 (March 2022) - Small, Kirsten A.; Sidebotham, Mary; Fenwick, Jennifer; Gamble, Jenny
Abstract: Background: Central fetal monitoring systems transmit cardiotocograph data to a central site in a maternity service. Despite a paucity of evidence of safety, the installation of central fetal monitoring systems is common. Aim: This qualitative research sought to explore whether, and how, clinicians modified their clinical safety related behaviours following the introduction of a central monitoring system. Methods: An Institutional Ethnographic enquiry was conducted at an Australian hospital where a central fetal monitoring system had been installed in 2016. Informants (n = 50) were midwifery and obstetric staff. Data collection consisted of interviews and observations that were analysed to understand whether and how clinicians modified their clinical safety related behaviours. Findings: The introduction of the central monitoring system was associated with clinical decision making without complete clinical information. Midwives' work was disrupted. Higher levels of anxiety were described for midwives and birthing women. Midwives reported higher rates of intervention in response to the visibility of the cardiotocograph at the central monitoring station. Midwives described a shift in focus away from the birthing woman towards documenting in the central monitoring system. Discussion: The introduction of central fetal monitoring prompted new behaviours among midwifery and obstetric staff that may potentially undermine clinical safety. Conclusion: This research raises concerns that central fetal monitoring systems may not promote safe intrapartum care. We argue that research examining the safety of central fetal monitoring systems is required.